Who Won the Science Wars? - Polšek, Darko (Array, 2009)
Bogdanov affair in astrophysics is strikingly similar to Sokal’s in "cultural studies". This paper discusses similarities between Sokal and Bogdanov affairs, especially the outrageous methods and behaviour of brothers Bogdanov, and concludes that the latter affair has shown that natural sciences and natural scientists are not beyond reproach, beyond criteria of cogency, validity and criticism, as was once suggested by Sokal’s affair. This has a broader morale: since "high science" is understood by fewer scholars, such science is sometimes more prone to outrageous hypothesis which would not be tolerated in the more common ones. Therefore, there has to be at least a symmetry in critical approach to scientific claims: neither the type of science, nor the fame of scientists should provide a guarantee of proper conduct and scientific methodology. The paper discusses various meanings of symmetry in scientific approach to science, and discussing "trust" and "distrust" in science suggests a description of the s.c. "circle of credibility".